Collaboration in the revision of a piece of writing: An analysis of group revision sessions with university students - Bea Reyes, Aranzazu; Rodríguez-Gonzalo, Carmen (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2025)
The importance of revision has been recognised by numerous scholars of the teaching and learning of writing (Abad & Rodríguez-Gonzalo, 2023; Bereiter & Scardamalia, 1987; Camps, 2020; Horning & Becker, 2006), especially if it is understood as a recursive and transversal phase that affects all levels of language (Álvarez Angulo, 2011; Camps, 2020; Marin & Legros, 2006). To test whether group revision is an effective tool in the teaching-learning process of writing in Spanish as a first language, in this paper we analyse large group revision sessions recorded in the natural context of a university classroom in which we implemented a didactic writing sequence (Camps, 2020; Dolz et al., 2001; Rodríguez-Gonzalo & Abad-Beltrán, 2023). The objective of this paper—an instrumental case study (Stake, 2007; Yin, 2009)—is to describe the interactions that take place in this revision process, categorise the aspects of the different linguistic levels to be identified and describe the students' proposed actions aimed at modifying the texts. The results show that approaching the revision phase collectively encourages the development of the students' metalinguistic and meta-rhetorical awareness (Horning, 2006), provided that this phase is not limited to the correction of errors in the final text and is conceived as a complex process that represents growth, progress and discovery (Haar, 2006) in the composition of a piece of writing.